The 3-D shallow velocity structure and sedimentary structure of 2017 Ms6.6 Jinghe earthquake source area derived from dense array observations of ambient noise - Zhou, Ming; Tian, Xiaofeng; Yang, Zhuoxin; Liu, Qiaoxia; Gao, Zhanyong (Frontiers in Earth Science, 2023)
To understand the shallow structure and complex sedimentary environment of the 2017 Jinghe Ms6.6 earthquake focal area, we used one mouth of continuous sesimic data from a dense seismic array of 208 short period stations around the earthquake focal area, and applied the ambient noise tomography (ANT) method to image the three-dimensional Shear wave velocity structure at the depth less than 4 km. The shear wave velocity shown clear lateral variations and vertical variations from the surface to the deeper regions and has a tight correlation with surface geological and tectonic features in the study area. Obvious low-velocity anomalies has been presented throughout most of the Jinghe depression, whereas the Borokonu Mountains presented high-velocity anomalies. The thickness of the Cenozoic sedimentary basement in the study area is approximately 1–4 km, and the distribution of thickness is highly uneven. The crystalline basement in the study area has strong bending deformation, and the non-uniform Cenozoic sediments are related to the strong bending deformation of the crystalline basement. The Kusongmuchik piedmont fault is a high-angle thrust fault cutting through the base. There are also many medium low-angle faults, which do not penetrate the surface, which has indicated that they are in a concealed state at present. The results have provided a shallow high-resolution 3D velocity model that can be used in the simulation of strong ground motion and for evaluating potential seismic hazards.